Face to Face Sales and Sales Promotions have a Positive Effect on Gold Jewelry Purchasing Decisions - Tarsisius Kana (International Journal of Social Science and Business, 2020)
Purchasing decisions are influenced by various factors, both internal and external factors. Face-to-face selling and sales promotion are two factors that can influence purchasing decisions. This study aims to analyze the influence of face-to-face sales and sales promotions on purchasing decisions for gold jewelry. This research is a a quantitative approach research. The population used in this study amounted to 1,193 consumers. The sampling method used was accidental sampling, in order to obtain a sample of 92 people. The data were collected using interview techniques and questionnaires. The collected data were analyzed using multiple linear regression analysis techniques using SPSS version 22 statistical tools. The results showed that face-to-face sales and sales promotion variables together had a positive effect on purchasing decisions. This can be proven from the results of F-count (195.569) higher than F-table (3.10) with a significance level of 0.000 less than 0.05, then Ha is accepted and H0 is rejected. It can be concluded that in simultaneously, there is a significant and positive influence between face-to-face sales and sales promotion on gold jewelry purchasing decisions.